Pengaruh Return on Assets dan Debt to Equity Ratio terhadap Harga Saham pada Institusi Finansial di Bursa Efek Indonesia - Rani Ramdhani (Bina Nusantara University, 2013)
This study aims to determine the effect of Return on Assets and Debt to Equity Ratio of Stock Price on Financial Institutions in Indonesia Stock Exchange. This study used secondary data, with samples 2 financial companies in Indonesia Stock Exchange during the study period 2004-2010. Independent variables in this study are Return on Assets and Debt to Equity Ratio. This study used purposive sampling technique. The method of data analysis used classical assumption test, hypothesis test, multiple regression analysis, the F test and t test. Based on results of the study, Return on Assets and Debt to Equity Ratio have no significant effect on stock price. Meanwhile, the F test result shows that Return on Assets and Debt to Equity Ratio jointly have no effect on stock price.